Neutron reflectometry analysis of Li4Ti5O12/organic electrolyte interfaces: characterization of surface structure changes and lithium intercalation properties. Issue 20 (19th September 2016) - Hirayama, Masaaki; Shibusawa, Takumi; Yamaguchi, Ryo; Kim, KyungSu; Taminato, Sou; Yamada, Norifumi L.; Yonemura, Masao; Suzuki, Kota; Kanno, Ryoji
Abstract: Abstract : The structure changes and lithium intercalation properties in the surface region of Li4 Ti5 O12 were investigated using epitaxial Li4 Ti5 O12 (111) film model electrodes. The discharge–charge measurements, which were conducted with 1 mol/dm 3 LiPF6 -containing propylene carbonate, revealed that a 23.8 nm-thick film exhibited a small capacity of 115 mA h/g compared to the theoretical value of 175 mA h/g. In situ neutron reflectometry and ex situ x-ray diffractometry and reflectometry indicated that an irreversible phase change had occurred in the 10-nm surface region of Li4 Ti5 O12 during the initial reaction processes. The level of deterioration of the surface structure was significantly reduced by decreasing the LiPF6 concentration; in addition, side reactions of the cell components with the electrolyte species, and their products, may be associated with the deterioration of the Li4 Ti5 O12 surface. The surface reactions have a significant impact on the capacity of lithium intercalation in nano-sized Li4 Ti5 O12 .